Computed tomographic demonstration of calcification of the ligamenta flava of the lumbosacral spine in ankylosing spondylitis. Issue 1 (January 1988) - Avrahami, E; Wigler, I; Stern, D; Caspi, D; Yaron, M
Abstract : An axial computed tomographic (CT) scan of the lumbosacral regions was performed in 65 patients. The patient population was divided into two groups. The first (control) group included 40 elderly patients without calcification of the ligamenta flava. The second group included 25 patients with ankylosing spondylitis. More than 90% of those in the second group showed calcified lumbosacral ligamenta flava. In two patients these calcifications produced spinal stenosis. The diagnostic and practical importance of these findings are discussed.